The cancer care experiences of gay, lesbian and bisexual patients: A secondary analysis of data from the UK Cancer Patient Experience Survey. (27th February 2017) - Hulbert‐Williams, N. J.; Plumpton, C.O.; Flowers, P.; McHugh, R.; Neal, R.D.; Semlyen, J.; Storey, L.
Abstract : Understanding the effects of population diversity on cancer‐related experiences is a priority in oncology care. Previous research demonstrates inequalities arising from variation in age, gender and ethnicity. Inequalities and sexual orientation remain underexplored. Here, we report, for the first time in the UK, a quantitative secondary analysis of the 2013 UK National Cancer Patient Experience Survey which contains 70 questions on specific aspects of care, and six on overall care experiences. 68, 737 individuals responded, of whom 0.8% identified as lesbian, gay or bisexual. Controlling for age, gender and concurrent mental health comorbidity, logistic regression models applying post‐estimate probability Wald tests explored response differences between heterosexual, bisexual and lesbian/gay respondents. Significant differences were found for 16 questions relating to: (1) a lack of patient‐centred care and involvement in decision‐making, (2) a need for health professional training and revision of information resources to negate the effects of heteronormativity and (3) evidence of substantial social isolation through cancer. These findings suggest a pattern of inequality, with less positive cancer experiences reported by lesbian, gay and (especially) bisexual respondents. Poor patient–professional communication and heteronormativity in the healthcare setting potentially explain many of the differences found. Social isolation is problematic for this group and warrants further exploration.